The pathogenetic substantiation for using ozone therapy in patients of the puerperal period complicated by Gram-negative sepsis - Boyarinov, Gennadiy Andreevich; Boyarinova, Larisa Valentinovna; Kucherenko, Victoria Evgenievna; Zaytsev, Roman Romanovich (Journal of Health Inequalities, 2015)
The study involved 29 patients of the puerperal period complicated by Gram-negative abdominal sepsis. The complex intensive therapy for the postoperative patients included the daily intraaortal infusion of 400 ml of ozonated saline solution (OSS) at the ozone concentration of 10.5 mg/l within 5 days. On the first and on the fifth day after surgery the content of gram-negative bacteria lipopolysaccharide (LPS) in blood, metabolism products of nitrogen oxide (NO) – nitrites and nitrates, substances with low and medium molecular weight (SL&MMW) in plasma, erythrocytes and urine was determined before, at the end of and 1 and 4 hours after the OSS infusion. It was found that the main pathogenetic mechanisms of the ozone therapy for patients with Gram-negative sepsis was the direct oxidative effect of ozone on the Gram-negative bacteria LPS and SL&MMW and that the LPS oxidative breakdown with ozone causes the decrease in the NO production and, therefore, to the reduced contents of nitrates and nitrites.